Editorial [Hot Topic: Targeted Alpha Therapy - Part II (Guest Editor: Jorgen Elgqvist)] - Elgqvist, Jorgen (Current Radiopharmaceuticals, 2011)
The Magic-Bullet: Moving the Concept Towards Reality - Part II As already mentioned in Part I of these two hot-topic issues for Targeted Alpha Therapy (TAT), the possibility of pinpointing biological targets, and thereby potentially targeting and eradicating small tumors or even single cancer cells, is a tantalizing concept that has been discussed since the magic-bullet concept was first presented by Paul Erlich in the beginning of the 20th century in connection with his work on tissue staining for histological examinations and the work by Kohler and Milstein on antibody production published in 1975. As discussed in Part I, this concept now seems feasible partly due to the use of highly specific protein targeting constructs (Olafsen et al., Curr. Radiopharm., 2011, 4(3), 197-213), and refined radiochemical labeling techniques (Wilbur, Curr. Radiopharm., 2011, 4(3), 214-247, and Lindegren et al., Curr. Radiopharm., 2011, 4(3), 248- 260). In Part I the production of radionuclides suitable for TAT was also discussed (Zalutsky et al., Curr. Radiopharm., 2011, 4(3), 177-185, and Haddad et al., Curr. Radiopharm., 2011, 4(3), 186-196) as well as some dosimetric aspects of alpha(α)- particles (Sgouros et al., Curr. Radiopharm., 2011, 4(3), 261-265, and Chouin et al., Curr. Radiopharm., 2011, 4(3), 266-280). The use of α-particles, having a linear energy transfer (LET) typically of about 100 keV/μm and, therefore, a high probability of causing double strand breaks (DSB) and hence killing cells along its track, is very promising. The short range of the α- particles (maximum ∼80 μm in tissue) makes them even more interesting by minimizes unwanted irradiation of normal tissue surrounding the targeted cancer cells, assuming high specificity of the targeting construct and good stability of the chemical bonds between the targeting construct and the α-particle emitter. If specificity or penetration of the radioimmunoconjugate into tumor tissue is not good enough though, heterogeneous distribution of the radioimmunoconjugates will occur (and hence a heterogeneous absorbed dose distribution) and the short range of the α-particles will be a drawback. The need for developing targeting constructs with high specificity must therefore be emphasized, although the bystander effect potentially could decrease the unwanted effect of heterogeneous cancer cell killing in a tumor to some degree. The importance of improving the specific activity of the injected solution should also not be underestimated, especially important when treating low antigen-expressing cancer cells. It is very encouraging to see an increasing clinical experience with TAT, although the pace with which it does could preferable be higher. The clinical experience includes gliomas, ovarian cancer, metastatic melanoma, metastatic prostate cancer, lymphoma, and acute myeloid leukemia. Further clinical trials, e.g. phase II trials, are to a large extent dependent on governmental support and funding, and one of the aims of these two hot-topic issues is therefore to summarize and to show the potential of TAT for the relevant authorities. In this issue, the last of these two hot-topic issues for TAT, articles discuss the recent developments in the applications of 211At, 223Ra, 213Bi, and 225Ac, the toxicity of α-particle emitting radioimmunoconjugates, patient specific α-particle dosimetry, and the future prospects for TAT. In the first article, Vaidyanathan et al. discusses 211At and 223Ra and their applications in TAT. The authors say that 211At probably is the most versatile based on its half life, decay scheme and chemistry. But for targeting bone metastases, they indicate that 223Ra is the ideal radionuclide because simple cationic radium can be used for this purpose. The second article by Morgenstern et al. discusses the applications of 213Bi in TAT and describes methods for the production of 225Ac and 225Ac/213Bi radionuclide generators. The article gives an overview of selected preclinical studies and summarizes the current clinical experience with 213Bi. Scheinberg et al. presents different therapeutic applications of 225Ac and mentions for example that it has been developed into potent targeting drug constructs and is in clinical use against acute myelogenous leukemia. The forth article, by Dahle et al., discusses the normal tissue toxicity and relative biological effectiveness (RBE) of α-emitting radioimmunoconjugates, and conclude by for example saying that RBE is useful preclinical information that should be taken into consideration when designing clinical trials of TAT. In the article by Palm et al. the patient dosimetry related to TAT is discussed. Similarities and differences compared to conventional therapies using β-particle emitters are mentioned, and the specific challenges of establishing accurate dosimetry for α-particles in the individual patient are presented. In the concluding article by Barry Allen the future prospects of TAT are presented. The strengths and weaknesses of TAT are examined and the way forward for clinical acceptance is discussed. For example, tumor antivascular α-therapy (TAVAT) for solid tumors is mentioned by the author as one way to extend the promise of TAT.....